A scatter of light eaudiobook - Lo, Malinda (Listening Library, 2022)
“Full of yearning, ponderances about art and what it means to be an artist, and self-revelation, A Scatter of Light has a simmering intensity that makes it hard to put down."—NPR An Instant New York Times Bestseller Last Night at the Telegraph Club author Malinda Lo returns to the Bay Area with another masterful queer coming-of-age story, this time set against the backdrop of the first major Supreme Court decisions legalizing gay marriage.  Aria Tang West was looking forward to a summer on Martha’s Vineyard with her best friends—one last round of sand and sun before college. But after a graduation party goes wrong, Aria’s parents exile her to California to stay with her grandmother, artist Joan West. Aria expects boredom, but what she finds is Steph Nichols, her grandmother’s gardener. Soon, Aria is second-guessing who she is and what she wants to be, and a summer that once seemed lost becomes unforgettable—for Aria, her family, and the working-class queer community Steph introduces her to. It’s the kind of summer that changes a life forever. And almost sixty years after the end of Last Night at the Telegraph Club , A Scatter of Light also offers a glimpse into Lily and Kath’s lives since 1955.